Deformation Behaviour of Erodible Soil Stabilized with Cement and Quarry Dust - Emeka, Arinze Emmanuel; Jonah Chukwuemeka, Agunwamba; Benjamin.Okwudili, Mama (Ital Publication, 2018)
This study was carried using finite element software (Plaxis) in studying the Engineering behavior of erodible soil-quarry dust composite at a proportion of 50% quarry dust and 10% cement. It discusses the effects of decorative street light through numerical analysis using the Finite Elements Method. Plaxis program v8.2 was applied to model the soil behavior. The Mohr-Coulomb model reveals that the deformations are concentrated exclusively on the base course, with the appearance of plastic tension cut-off points on base course. The structure was subjected to double point loads of 50 kN/m each which resulted to 100 kN/m. The results shows that the pavement deformed at load 85.16kN/m which showed that the soil strength cannot withhold the pressure from the street light. The load displacement acting on the base of the highway in study is . The result also shows that failure was concentrated at the base course of the pavement. This was due to the presence of underground water beneath the phreatic level. The quarry dust is a good replacement to weak soil or a good additive to help improved a problematic soil. From analysis, the soil strength lies below the effective stress acting on the pavement which is equal to 85.16 kN/m. It is advisable to replace some quantities of the existing soil and be replaced by quarry dust since quarry dust is a waste product from crushing of stones. Lastly, about 30% of the existing soil should be replaced by either the mixture of lateritic soil and quarry dust or the soil there should be used as subbase which may not be economical.